MANFAAT PEMBELAJARAN ROBOTIKA UNTUK BELAJAR SISWA DI SEKOLAH DASAR - Korni Mufarola; Anggiat Rio Murbowo (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Robot technology and applications continue to develop rapidly. However, designing robots must overcome several problems. Control is closely related to strategies that allow a computer to play a role as a brain in the control system directing the movements of a controlled device, and receiving a response from the sensors that are owned by the controlled tool to the computer. A robot is an electro-mechanical or bio-mechanical device, or a combination of equipment that produces autonomous movements and based on the movements that are ordered